Heterotopic ossification following anterior shoulder dislocation. (8th November 2018) - Patel, Preemal; Brkljac, Milos; Sonar, Ulhas; Kumar, Shyam
Abstract : Heterotopic ossification (HO) is the abnormal growth of extraskeletal bone. Joint involvement may result in chronic stiffness and pain causing considerable functional impairment and the inability to perform the activities of daily living. HO affecting the shoulder joint is rare and little is known about its clinical course or treatment. Here, we describe the first reported case of glenohumeral HO following anterior dislocation. This occurred in a 70-year-old man following a fall onto outstretched hand. Due to persistent stiffness and pain at 8 months from initial injury, he underwent plain radiographs and MRI scans that confirmed rotator cuff tear and HO. He was managed conservatively with physiotherapy and non-steroidal anti-inflammatory drugs. At 1-year follow-up, the patient maintains a good functional outcome.